Development of a Web-Based Thesis Repository for Information Technology Education Students - Permana, Ryan; Alkadri, Syarifah Putri Agustini (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
This study aims to develop a Web-Based Thesis Repository System for the Information Technology Education Study Program at Universitas PGRI Pontianak. The system was designed to address challenges in manual thesis archiving and limited accessibility for students seeking academic references. The research employed the Research and Development (R&D) approach using the ADDIE model, which includes five systematic stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through expert validation and user feedback. The system provides key features such as user registration, secure login, thesis upload, metadata management, and advanced search functionality. Validation results from two product experts and one content expert indicated that the system achieved an average product score of 3.34 and a content score of 3.38, both categorized as “Good.” The findings demonstrate that the developed repository is feasible, efficient, and effective in managing digital thesis data while enhancing accessibility and transparency in academic information retrieval. This repository supports digital transformation in higher education by promoting sustainable knowledge management and improving research visibility. The system is recommended for broader implementation and future development through integration with institutional databases and cloud-based storage for enhanced scalability and security.